2015
DOI: 10.1186/s12905-015-0224-z
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular response to short-term fasting in menstrual phases in young women: an observational study

Abstract: BackgroundMenstrual cycle-related symptoms are an important health issue for many women, and some may affect cardiac autonomic regulation. In the present study, we evaluated the cardiovascular and physiological stress response to 12-h short-term fasting in the menstrual phases of healthy young women.MethodsWe performed a randomized crossover study. Subjects were seven female university students (age: 22.3 ± 1.0 years). The experiments comprised four sessions: meal intake in the follicular phase, meal intake in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 52 publications
1
23
1
Order By: Relevance
“…In addition, the validity of the self-reported measures was related to the menstrual cycle phase. The discrepancy with previous research showing no relationship relating to menstrual cycle in students 18–24 years [28] should be attributed to the differing choice of specific phases for physiological characteristics [29] to the present study. From a physiological point of view, energy intake and expenditure increases in the luteal phase compared to the follicular phase leading to increased frequency of cravings for foods [30].…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, the validity of the self-reported measures was related to the menstrual cycle phase. The discrepancy with previous research showing no relationship relating to menstrual cycle in students 18–24 years [28] should be attributed to the differing choice of specific phases for physiological characteristics [29] to the present study. From a physiological point of view, energy intake and expenditure increases in the luteal phase compared to the follicular phase leading to increased frequency of cravings for foods [30].…”
Section: Discussioncontrasting
confidence: 99%
“…A total of 45 studies published between the year 1995 and October 2018 were included in the systematic review [40,42,43,44,45,49,50,51,52,53,54,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90]. Only one of the 45 studies was published in Russian [43]; all others were written in English.…”
Section: Resultsmentioning
confidence: 99%
“…Out of these 38 studies, only one study [57] did not compare a phase of the follicular half with a phase of the luteal half, but assessed the menstrual and the ovulatory phase (two follicular phases). The remaining 37 studies reporting quantitative data could be included in the meta-analytic comparison of the follicular and the luteal phase which is based on 1004 females [40,42,43,44,45,50,52,53,54,58,59,61,62,63,64,65,66,67,68,70,71,72,73,74,75,76,77,78,80,82,84,85,86,87,88,89,90].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that reduced dietary fat intake increased parasympathetic activity in women [3] and reduced blood pressure in individuals with abdominal obesity [4]. Additionally, effects of 12 h of fasting on heart rate variability and blood pressure during the menstrual phases in women were previously demonstrated [5]. Furthermore, de Jonge et al [6] reported, in overweight individuals, improved vagal activity and reduced sympathetic activity after six months of caloric restriction combined with exercise, despite weight loss comparable to caloric restriction only.…”
Section: Introductionmentioning
confidence: 99%